2004
DOI: 10.1007/s00424-004-1282-5
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression of fibroblast growth factors and hepatocyte growth factor in rat plantaris muscle following denervation and compensatory overload

Abstract: We addressed the question of whether hypertrophy induced by compensatory overload differs according to innervation status, and how fibroblast growth factors (FGF) and hepatocyte growth factor (HGF) mRNAs are expressed in the rat plantaris muscle during overload (OL) and/or denervation. Male Wistar rats were divided into four groups (Normal-Cont, Normal-OL, Denervated-Cont, and Denervated-OL). according to the plantaris denervation and/or overload. Three weeks later, plantaris weight in Denervated-Cont and Dene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…1,12,22 Yamaguchi et al 27 addressed the questions of whether hypertrophy induced by compensatory overload differs according to innervation status and how FGF mRNA is expressed using a rat model during overload or denervation. They found that the gene expressions of members in the FGF family differed significantly in response to different stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…1,12,22 Yamaguchi et al 27 addressed the questions of whether hypertrophy induced by compensatory overload differs according to innervation status and how FGF mRNA is expressed using a rat model during overload or denervation. They found that the gene expressions of members in the FGF family differed significantly in response to different stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that HGF is present in the extracellular matrix s u r r o u n d i n g m u s c l e f i b e r s 1 6 , 4 8 ) , o r immunolocalized at regenerating skeletal muscle 49) . In situ hybridization has also revealed HGF mRNA in regenerating muscle fibers 15,31) . In the present study, HGF was clearly immunolocalized in the cytoplasm of satellite cells early in the recovery process, strongly suggesting that HGF is produced by local satellite cells in response to reloading stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have examined the role of HGF during maturation and regeneration of skeletal muscle, few attempts have been made to examine changes in HGF expression in hypertrophied and atrophied muscle in vivo. Only the content of HGF mRNA expression following denervation and compensatory overload 31) , and of HGF protein following skeletal muscle injury 32) , have been reported. These reports did not examine changes in HGF protein content following changes in muscle activities.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell et al 11) noted that stretch-induced hypertrophy led to an increase in bFGF mRNA levels in avian muscles and that bFGF localized the perimysium and endomysium of the myofiber periphery. Yamaguchi et al 21) reported that the expression of bFGF mRNAs increased shortly after the initiation of compensatory overload and decreased consequent to denervation. Kästner et al 22) described the enhancement of satellite cell proliferation upon the introduction of bFGF to cultured rat myofibers.…”
Section: Discussionmentioning
confidence: 99%